Applying the post-digital strategy of anexact architecture to non-standard design practices within the challenging construction contexts. Issue 8 (August 2022) - Wang, Sining; Lin, Dandan
Abstract: New architectural forms offered by digital design approaches often appear incompatible with the prescribed precision and control in construction, especially in developing regions where advanced implementation means are limited. In response, this paper suggests working with design practice indeterminacy. Named 'anexact architecture', the post-digital design practice strategy presents a convergent diagram of seeking the feasible design solution space. It relies on the procedural parametric modelling to constantly integrate computation and humanisation, so that a rigorous built outcome is capable of accommodating project-specific idiosyncrasies and constraints. The demonstrator projects are discussed based on the combination of the Participatory Action Research method and the idea of anexact architecture. This paper aims to illustrate the peculiarity of anexact architecture and its ideology of treating design delivery uncertainties as essentials rather than negatives when practicing in a volatile construction context. Abstract : Design practice strategy; Post-digital architecture; Parametric design; Developing region; Non-standard architecture.